Impact of Spatial Planning at Alun-Alun Gianyar - Daniswara, I Gusti Putu Bagus; Dwijendra, Ngakan Ketut Acwin (Universitas Ibn Khaldun Bogor, 2026)
Alun-Alun Kota Gianyar is a public space located at the center of Gianyar City. It is frequently utilized by the local community for sports, relaxation, and recreation. In 2020, the Gianyar Regency Government decided to renovate and redesign the square. The development of Alun-Alun Kota Gianyar has led to emerging business opportunities, as evidenced by the increasing number of shops and commercial activities around the area. This study aims to illustrate the role of Alun-Alun Kota Gianyar as a public space in stimulating economic growth, particularly through the increase of community income, the creation of new job opportunities, and the emergence of local businesses. The research adopts a qualitative descriptive method, with data obtained through direct observation and interviews with visitors and business actors around Alun-Alun Kota Gianyar. The objective is to examine the economic impact of the square, particularly for local entrepreneurs. The findings indicate that Alun-Alun Kota Gianyar has positively influenced the economic growth of local business actors. The data reveals a shift in business functions around the square before and after the renovation, along with a 14.9% increase in profits for stall and shop owners, and an 18.1% increase for street vendors (PKL), driven by the higher number of visitors attracted to the area.